P162 Prevalence and incidence of nonalcoholic fatty liver disease in Inflammatory Bowel Disease patients: risk factors for progression. (21st January 2022) - Crispino, F; Brinch, D; Scrivo, B; Celsa, C; Di Grado, G; Sapia, A; Petta, S; Cappello, M
Abstract: Background: Cross-sectional studies have assessed the prevalence of non-alcoholic fatty liver disease (NAFLD) in patients with inflammatory bowel disease (IBD). However, longitudinal studies are more suitable to capture dynamic changes. Our aim was to investigate the prevalence and progression of NAFLD in a cohort of IBD patients using validated non-invasive tools. The role of metabolic, disease-related and genetic factors as predictors of NAFLD was also assessed. Methods: IBD patients without known chronic liver disease were enrolled between 2019 and 2021. NAFLD was defined as Hepatic Steatosis Index (HSI) ≥ 36 or controlled attenuation parameter (CAP) ≥288 dB/m. Demographic data, traditional risk factors for NAFLD, biochemical tests and disease features were retrospectively collected in a dedicated database at the time of IBD diagnosis (defined as baseline) and at the last follow-up visit. PNPLA3 rs738409 C>G and TM6F2 E167K C>T polymorphisms were also investigated. Univariate and multivariate logistic regression analysis were performed to identify risk factors for NAFLD at baseline and at the end of follow-up. Results: 227 consecutive patients (mean age 46.1 ± 13.4 years, 48.7% males, 57% Crohn's disease, mean disease duration 9.4 ±7.5 years) were enrolled. Laboratory data at the time of diagnosis were available for 64 patients. The mean HSI was 30.9 ± 4.9 and 8/64 eligible patients (12.5%) had NAFLD at baseline. Male sex (odds ratio [OR]: 5.6; 95% confidence interval [CI] 3.1–8.9; P = 0.02) and body mass index (BMI) (OR: 1.4, 95% CI 1.1–2.9; P = 0.0008) were significantly associated with NAFLD at baseline. 11/64 (17.1%) patients developed NAFLD, accounting for an incidence rate of 4.0/100 PY; this was predicted only by changes in BMI over time (OR: 13.6, 95% CI 4.8–19.5; P = 0.001). At the last follow-up visit, NAFLD was diagnosed in 31.2% (71/227) according to HSI and in 21.1% (48/227) according to CAP. Among 8 patients with NAFLD at baseline, HSI worsened in 6 patients (41.0 ± 3.3 vs 44.0 ± 5.2), while two patients had steatosis regression. At the end of follow-up, age (P = 0.01), BMI (P = 0.002) and previous surgery (P = 0.01) were independently associated with NAFLD. Conclusion: Our study confirms that NAFLD is common in patients with IBD. Variables related to IBD were not associated with incident NAFLD. Age, BMI and previous surgery were independently associated with NAFLD progression, suggesting a pathogenetic role of gut microbiota and impairment in bile acids metabolism. Our results suggest the need for active surveillance for NAFLD in patients with IBD.